Inovasi Mitigasi Kebencanaan pada Desa Wisata Rindu Hati dalam Pembangunan Berkelanjutan - Novliza Eka Patrisia; Sri Indarti; Titi Darmi; Rifa i (JURNAL ABDIMAS SERAWAI, 2026)
Rindu Hati Village as a leading tourist village in Central Bengkulu faces a paradox between tourism potential and vulnerability to annual flood disasters that threaten the sustainability of its development. This community service developed an integrated disaster mitigation innovation model that combines digital technology approaches, local wisdom, and sustainable development principles. Through a 6-month participatory action research (PAR) method, involving 40 participants (village officials, community leaders, MSMEs, and academics), the following were carried out: (1) Community-based risk mapping involving 30 MSMEs and tourism awareness groups; (2) Trial of a simple IoT-based early warning system; (3) Development of a "Resilient Tourism" module that integrates disaster education in tourism packages. The main findings show that the tripartite collaboration model (village government, academics, and tourism communities) is able to increase adaptive capacity by 40% based on the village resilience index (average pretest score of 52.3 increased to 73.2 in the posttest). The integration of the RKDD as a disaster command center and tourism promotion center has successfully reduced disaster response time from 3 hours to 45 minutes (a 75% savings). Policy recommendations include: Formulation of a Village Regulation on Disaster-Safe Tourism Operational Standards; Allocation of 20% of village funds for the development of independent mitigation technology; Incentive schemes for tourism businesses that apply resilience principles. This service demonstrates that a tourism ecosystem-based mitigation approach not only reduces risk but also creates added economic value, while supporting the achievement of village SDGs 11 and 13.